Government And Community Collaboration in Strengthening Digital Administration Services in Ketegan Village, Taman District, Sidoarjo Regency - Rina Kharisma Wijayanti; Fedianty Augustinah; Eny Haryati (International Journal of Humanities and Social Sciences Reviews, 2025)
This research seeks to examine the partnership between government and community in enhancing digital administrative services in Ketegan Village, Taman District, Sidoarjo Regency. The research context centers on the local government's attempts to advance digital public service transformation, which encounter obstacles like low digital literacy, insufficient infrastructure, and poor collaborative governance at the village level. The study utilized a qualitative strategy featuring a case study technique, gathering data via in-depth interviews, participatory observation, Focus Group Discussions (FGDs), and reviews of policy documents related to Sidoarjo’s Smart City initiative. The results show that although digital infrastructure and institutional dedication are in place, execution is still obstructed by restricted technological capability, unreliable internet access, and poor public digital literacy. Collaboration between the government and community is starting to develop through local projects, but it remains informal and does not have a sustainable coordination structure. The research suggests improving the digital skills of officials and citizens, creating organized digital collaboration platforms in villages, and adopting participatory assessment methods to guarantee an inclusive and flexible digital transformation. These results are anticipated to act as a guide for local authorities in enhancing governance of digital-based public services.